Speciation of Biochemical Oxygen Demand (BOD) for wastewater and surface water / Norizan Abdullah - Abdullah, Norizan (2013)
The Biochemical Oxygen Demand (BOD) test has been a standard test method to quantify the amount of biodegradable organic matter present in a water sample. The test is typically conducted over a 5-day period (BODs), with the sample being incubated at 20°C. This study aims to speciate the two organic fractions under two distinct categories termed slow-BOD and fast-BOD. Furthermore, the cBOD test also being conducted. The speciation is done by filtering the samples with filter size of 0.12 pm to separate the dissolved and particulates fractions. Twenty four of samples from variety sources have been collected and tested. The samples have been divided into five category which are discharge from sewage treatment plant (STP), industrial discharge, sullage, leachate and river water. The results showed that the speciation of slowly biodegradable fraction and fast biodegradable fraction are obviously shown in the BOD and cBOD reaction. It also has been found that five samples out of twenty four samples showed that the degradation of organic matter present is between 70-80 % in 5 days. The rest of the sample showed the degradation of the organic matter is below than 70%. Furthermore, the kinetic reaction parameter of BOD had been calculated through four different methods which are Thomas, Least-square, Fujitomo and Slope methods. From the observation, least-square is the best method followed by slope, Fujitomo and Thomas method. The kinetic reactions support the finding which the speciation of slow-BOD and fast-BOD are obviously shown in this study.